Hydrodynamic and microbiological characterisation of free ground water in the city of Bafoussam, (West Cameroon). Issue 6 (24th May 2022) - Nguedia Djatsa, Kevin; Ndongo, Barthelémy; Ntankouo Njila, Roger; Kagou Dongmo, Armand
Abstract: The work presented here aims to carry out a physical characterisation of soils to understand their hydrodynamic behaviour and estimate the susceptibility of each group of soils to microbiological pollution. The field work associated with the laboratory work consisted of monitoring the hydrodynamic behaviour of previously identified and selected well waters, measuring the permeabilities of the soil samples and analysing the bacteriological parameters of the sampled well waters. At the end of this work, the piezometric data show a dominant SE-NW and ENE-OSW flow direction. The water levels do not vary significantly between the wet and dry seasons. The granulometric analysis of the soils reveals CU>3 showing a spread out granulometry with very low permeabilities of the order of 1.58×10−7 m/s and moderately high permeabilities of the order of 1.86×10−5 m/s. The microbiological data show pollution of human origin with a high bacterial load in the rainy season represented by a maximum of 240 CFU of Escherichia coli exceeding the WHO standards for drinking water. The majority of the polluted samples come from soils developed on granites and basalts, which are the most susceptible to pollution, making the groundwater vulnerable. HIGHLIGHTS: Wells on ignimbritic formations are shallow in the rainy season compared to the dry season. The permeability of soils on granitic formations is of the order of 10−5 m/s, classified as moderately high. There is microbiological pollution of human origin in the town of Bafoussam. Soils on granitic and basaltic formations are more susceptible to pollution and therefore make groundwater vulnerable to pollution. Graphical Abstract